Secrets of the Oracle Database - Debes, Norbert (Apress, 2013)
The book is intended to complement the vast documentation from Oracle Corporation as well as articles found on Oracle’s Metalink support platform. Arguably, the omission of some features from Oracle’s documentation might be considered a documentation bug. Many features, especially among those for troubleshooting (e.g., events) and tracing, remain undocumented on purpose and for good reason, since Oracle Corporation rightfully suspects that they might backfire when used in the wrong situation or without fully understanding the implications of their use. Such features are not the subject of this book either. Instead, this text is centered on those undocumented features that provide significant benefit without compromising the integrity or availability of databases. In this book, a certain feature is said to be undocumented if the full text search of the documentation provided on the Oracle Technology Network2 web site does not yield any hint of the feature’s existence. A feature is said to be partially documented if the full text search does reveal that the feature exists, but significant aspects of the feature are undocumented, thus limiting the usefulness of the feature. Incomplete documentation often causes the need to investigate a feature, which constitutes a significant investment in time and thus money, to reveal the undocumented aspects through trial and error, searching the Internet, or Oracle’s Metalink support platform. A significant number of undocumented aspects unveiled in this text are not addressed by Metalink articles. This book is a highly technical book. I have spared no effort in making the material as easily accessible as possible by not assuming too much previous knowledge by the reader, adopting a clear writing style, and presenting many examples. An occasional humorous remark serves to intermittently stimulate the right brain and perhaps even trigger a grin, allowing the left analytical brain to rest for a moment before tackling more technicalities.